HPV-related Vulvar Diseases and Perspectives of p16INK4a Immunochemistry: A Review of the Literature. Issue 6 (November 2017) - Carrone, Angela; Riganelli, Lucia; Savone, Delia; Casorelli, Assunta; Merlino, Lucia; Pecorini, Francesco; Pecorella, Irene; Mancino, Pasquale; Piccioni, Maria Grazia; Benedetti Panici, Pierluigi
Introduction: Two different types of vulvar intraepithelial neoplasia (VIN), HPV-related and HPV-unrelated, should be considered as two separate entities with different management options. The incidence of HPV-related VIN is increasing worldwide and is implicated in carcinogenesis. Our objective is to investigate the use of p16 INK4a immunostaining or p16 INK4a /p53 double staining for the detection of HPV-related disease to overcome the problem that histological criteria often have significant overlap. Methods: A systematic literature search was carried out in the online databases PubMed, EMBASE, Cochrane Library, Clincaltrials.gov and Scopus. The key search terms were HPV, VIN, p16 INK4a immunochemistry and p53. Results: We found that nuclear and cytoplasmic immunostaining for p16 INK4a was intense and diffuse in HPV-associated lesions and weak and focal in normal vulvar epithelium, nondysplastic lesions, lichen sclerosus and keratinizing vulvar squamous cell carcinoma. p53 nuclear immunostaining was always negative in HPV-related disease. Conclusions: Our findings indicated that p16 INK4a or p16 INK4a /p53 immunoreactivity, along with histological diagnosis, could be a convenient means to adequately classify VIN and its connection to HPV infection. Therefore, the clear recognition of HPV-associated VIN would lead to an appropriate strategy of treatment and follow-up.